Effect of a water extract of Curcuma longa on emotional states in healthy participants - KAWASAKI, Kengo (Biosci Microbiota Food Health, 2018)
Physiological symptoms of mood disturbances, such as fatigue or anxiety, are closely related to inflammation in the central nervous system or the whole body. Curcuma longa is widely used as a dietary spice and has been reported to have anti-inflammatory activity. To investigate the effect of a water extract of C. longa (WEC) on emotional states, a randomized, double-blind, placebo-controlled, parallel-group study was conducted with healthy participants. Forty-eight participants were randomly assigned to receive five tablets containing 150 mg WEC and 0.40 mg bisacurone (L-WEC group), five tablets containing 900 mg WEC and 2.40 mg bisacurone (H-WEC group), or matching placebo tablets (placebo group) daily for 8 weeks. Participant emotional states were measured every 4 weeks using the Profile of Mood States (POMS). The changes from week 0 to week 8 in the fatigue score of the POMS were significantly lower in the L-WEC group than in the placebo group. This result suggests that daily intake of 150 mg WEC may positively influence emotional fatigue, and further investigation focused on emotional fatigue is needed.